Host cell cAMP-Epac-Rap1b pathway inhibition by hawthorn extract as a potential target against Trypanosoma cruzi infection - Ferri, Gabriel; Fernández, Lucía R.; Di Mario, Guillermo; Musikant, Daniel; Palermo, Jorge A.; Edreira, Martin M. (Frontiers in Microbiology, 2023)
The two drugs currently available for the treatment of Chagas disease, Benznidazole and Nifurtimox, have shown to be effective in the acute phase of the disease, however, the 60 to 90 days treatment displays high toxicity and unwanted side effects, presenting, in addition, a low efficacy in the chronic phase of the disease. For this reason, new more effective therapies are needed. In this regard, we have recently shown that the inhibition of the Epac-Rap1b pathway abolished cAMP-mediated host cell invasion by Trypanosoma cruzi. Interestingly, it has been described that vitexin, a natural flavone that protects against ischemia-reperfusion damage, acts by inhibiting the expression of Epac and Rap1 proteins. Vitexin can be found in plants of the genus Crataegus spp., traditionally known as hawthorn, that are of great interest considering their highly documented use as cardio-protectors. Pre-treating cells with an extract of C. oxyacantha produced levels of T. cruzi invasion comparable to the ones observed for the commercially available Epac1-specific inhibitor, ESI-09. In addition, extract-treated cells exhibited a decrease in the activation of Rap1b, suggesting that the effects of the extract would be mediated by the inhibition of the cAMP-Epac-Rap1 signalling pathway. Using HPLC-HRMS 2 , we could confirm the presence of vitexin, and other flavones that could act as inhibitors of Epac/Rap1b, in the extracts of C. oxyacantha. Most significantly, when cells were treated with the extract of C. oxyacantha in conjunction with Nifurtimox, an increased modulation of invasion was observed.